MASSIVE OPEN ONLINE COURSE ON ACADEMIC WRITING: MANAGEMENT OF STUDENTS' MOTIVATION TO STUDY - Elena M. Bazanova; Elena E. Sokolova (Высшее образование в России)
In the framework of the discourse on the MOOC influence on the higher education system the issues whose solution will contribute to overcoming the main MOOC problem namely students becoming less motivated to study are being analyzed. The role of MOOC in the higher education system is illustrated by the example of Scholarly Communication academic writing course included into the English for Research Publication Purposes Specialization available at the international MOOC platform Coursera. Possible criteria and MOOC analytics format on the basis of Scholarly Communication students' contingent statistical data monitoring are being discussed. The foundations of online courses students on MOOC platforms motivation increase are revealed and the ways of the given problem solution are suggested.